Oswald Schmiedeberg (1838–1921) - Helmut Greim (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Oswald Schmiedeberg was born in one of the former Baltic provinces of Russia. He studied medicine in Dorpat (Tartu) and joined the Institute of Pharmacology of Rudolf Buchheim in Dorpat. After promotion (1866) and habilitation (1868), he succeeded Buchheim as director of the institute. During this time, he further developed the experimental methods leading to the improvement of pharmacological knowledge introduced by Buchheim. In 1872, he became director of the Institute of Pharmakologie of the newly founded Kaiser-Wilhelm University in Strasbourg. He held this position for over 42 years until the end of the World War 1 when all Germans had to leave the former Reichsland Elsass-Lothringen. He settled next to his friend and colleague Naunyn in Baden-Baden, where he died in 1921. Holmstedt and Liljestrand’s (1963) History of Pharmacology and Toxicology noted, “Schmiedeberg was undoubtedly the most prominent pharmacologist of his time.” He had about 120 pupils, about 40 of them occupied pharmacology chairs throughout the world. In the USA, John Jacob Abel, after his return to the USA, became the “father of American pharmacology”. In 1873, Schmiedeberg, together with the pathologist Klebs (Prague) and the clinician Naunyn (Königsberg), founded the Archiv für experimentelle Pathologie und Pharmakologie. When Naunyn died in 1925, the periodical was named Naunyn–Schmiedeberg’s Archiv, from volume 110 onwards. In 1969, the designation “experimental pathology” was dropped, since nearly all papers submitted for some time past dealt with pharmacology. In 1883, Schmiedeberg published the Grundriss der Arzneimittellehre , the later edits with the title Grundriss der Pharmakologie in Bezug auf Arzneimittellehre und Toxikologie .